Subjective social status and inequalities in depressive symptoms: a gender-specific decomposition analysis for South Africa - Chipo Mutyambizi; Frederik Booysen; Per Stornes; Terje A. Eikemo (BMC, 2019)
Abstract Background Inequalities in mental health are a notable and well documented policy concern in many countries, including South Africa. Individuals' perception of their position in the social hierarchy is strongly and negatively related to their mental health, whilst the global burden of poor mental health is greater amongst women. This paper offers a first glimpse of the factors that shape gender-based health inequalities across subjective social status. Methods This study employs the cross-sectional 2014 South African Social Attitudes Survey (SASAS). The prevalence of depressive symptoms is measured with the aid of the CES-D 8-item scale, with analyses disaggregated by gender. Concentration indices (CI) are used to measure inequalities in depressive symptoms related to subjective social status. The study applies the Wagstaff decomposition to determine the factors that contribute to these gender-based inequalities. Results More than 26% of the study sample had depressive symptoms (95% CI 24.92-28.07). The prevalence of depressive symptoms is significantly more pronounced in females (28.46% versus 24.38%; p = 0.011). The concentration index for depressive symptoms is − 0.276 (95% CI -0.341 - − 0.211), showing large inequalities across subjective social status. The observed SSS-related inequality in depressive symptoms however is higher for males (CI = -0.304) when compared to females (CI = -0.240) (p = 0.056). The most important contributor to SSS-related inequalities in depressive symptoms, at 61%, is subjective social status itself (contributing 82% in females versus 44% in males). Other variables that make large contributions to the inequalities in depressive symptoms at 11% each are race (contributing 2% in females versus 25% in males) and childhood conflict (contributing 17% in females versus 4% in males). Conclusion Policy makers should target a reduction in the positive contribution of SSS to depression via the implementation of programmes that improve social welfare. Given the much greater contribution to inequalities among females, these policies should target women. Policies that protect children and especially the girl child from conflict can also be useful in reducing inequalities in depression related to subjective social status during adulthood. Overall, there is need for a multi-sectoral approach to address these inequalities.